Product and Location Analysis of Guest Purchase Decisions - Aswari, Novita Indri; Octafian, Ray (Pusat Riset dan Inovasi Nasional, 2022)
This research has purpose to analyze how the influence of product and location is also to identify which variables are the most dominant on purchasing decisions at Wee Nam Kee Restaurant Semarang. Data collection techniques were carried out by observation and questionnaires. The analytical method used was quantitative descriptive analysis method using the SPSS application for data processing. The results obtained from this study have a positive and significant effect between product and location on purchasing decisions and the most dominant variable is the Location variable.